1982
DOI: 10.1159/000207070
|View full text |Cite
|
Sign up to set email alerts
|

Haematological Aspects of Systemic Lupus Erythematosus: A Reappraisal Using Automated Methods

Abstract: Twenty-two haematological parameters were measured in 30 patients with systemic lupus erythematosus (SLE) at 110 patient attendances. Using a 10,000 cells per sample automated differential counter, the major abnormalities demonstrated were: lympho-penia, monocytopenia, eosinophilopenia (each of which showed strong correlation with steroid therapy) and increased numbers of cells of high peroxidase activity. Despite the common lymphocytopenia elevation of large unstained cells was noted in 20% of patients. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…The variability observed in SLE patients is consistent with the leukopenia and lymphopenia reported in the literature [27][29]. Previous array studies have reported significant differences between SLE PBMC and healthy subjects [12].…”
Section: Discussionsupporting
confidence: 89%
“…The variability observed in SLE patients is consistent with the leukopenia and lymphopenia reported in the literature [27][29]. Previous array studies have reported significant differences between SLE PBMC and healthy subjects [12].…”
Section: Discussionsupporting
confidence: 89%
“…Some authors, but not all, 40 have shown that lymphopenia correlates with disease activity. Fever, polyarthritis, as well as central and peripheral nervous system disease, in particular, are associated with lymphopenia.…”
Section: Lymphopeniamentioning
confidence: 99%
“…Previous studies have used these techniques to document abnormalities in haematological indices associated with RA (as compared with a disease control group of patients with ankylosing spondylitis (AS))6 and with SLE. 7 As technology advances, however, newer machines have replaced the Hemalog D (Technicon) counter used in these studies, and these second generation machines perform to different specifications. Moreover, they are no longer just a research tool but are now standard equipment in most major haematology laboratories.…”
mentioning
confidence: 99%